2021
DOI: 10.1186/s12888-021-03476-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between social capital and depression among critically ill patients: evidence from a cross-sectional study in rural Shandong, China

Abstract: Background With an increasing number of critically ill patients, attention should be paid to both their physical health and mental health. The objective of this study is to examine the links between depression and social capital among critically ill patients. Methods Data for 1043 patients with critical illnesses was collected with a stratified cluster random sampling method in rural Shandong, China. Depression symptoms were measured using a short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…In addition, previous studies on the MPI did not consider the social capital dimension [56,60]. However, several studies have confirmed the negative impact of it on health poverty [61]. In this study, the social capital weight value was ranked sixth.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, previous studies on the MPI did not consider the social capital dimension [56,60]. However, several studies have confirmed the negative impact of it on health poverty [61]. In this study, the social capital weight value was ranked sixth.…”
Section: Discussionmentioning
confidence: 58%
“…treatment, showed great geographic variances in China. These geographic variances may be caused by geography-related differences in health behaviour (like alcohol usage and physical exercise) (28,29), available social support and social capital (like social trust in relatives and friends, distance to the nearest medical institution, and medical assistance from non-spouse) (30)(31)(32), the prevalence of multimorbidity (25), and economic development [including average household income (25,33), economic welfare and social service welfare (34), and the probability of being to left-behind children (35) or empty-nest elderly (7)]. In addition, as for the 10.3389/fpsyt.2023.1063328 geographic difference in the prevalence of depression, evidence also suggested that higher altitude is more likely to be associated with symptoms of depression, with a possible mechanism that increased altitude is associated with low-pressure hypoxia, which may alter the way the brain works (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Better education, higher economic status, and better marital status were protective factors for depressive symptoms, with high education levels potentially inhibiting inflammatory cytokine expression and improving cognition to decrease the prevalence of depression ( 14 ). Economic status is associated with life conditions and social capital, which could contribute to depressive symptoms ( 15 ). Marital status is related to social support, and positive social support can lower the risk of developing depressive symptoms ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Education, economic status, and marital status are generally reported to be significantly associated with depressive symptoms ( 10 ). High education levels are linked to decreasing the prevalence of depression ( 14 ), and better economic status is usually associated with better mental health conditions ( 15 ). In addition, married individuals generally have a lower prevalence of depressive symptoms ( 9 ).…”
Section: Introductionmentioning
confidence: 99%